Dezesseis de julho: festa, memórias e vivências na cidade de Borda da Mata - MG - Costa, Cleyton Antônio da (2015)
The search for "Sixteen July: Party, memories and experiences in the city of Borda da Mata - MG" aims to understand and discuss the different meanings and party senses, which contains two parts, one dedicated to the patron saint of the city, Our Lady of Carmo, and the other the administrative political emancipation, held in the city of Borda da Mata in the South of Minas Gerais, on 16 July. The study was conducted through oral history, with crossing with other sources, which enabled us to engage with many memories and other stories of different generations and meanings of the celebration, as well as the continuities and ruptures of this cultural practice that is permeated values, feelings and tensions. Configuring an upgraded tradition every year, means that the party is not something crystallized, motionless, is yes live dynamic and sustained by constant construction of senses and meanings, which are produced by different social experiences